Temporal Lobe Necrosis Following Radiotherapy in Nasopharyngeal Carcinoma: New Insight Into the Management - Zhou, Xin; Liu, Peiyao; Wang, Xiaoshen (Frontiers in Oncology, 2021)
Cerebral radiation necrosis (CRN) is a well-documented late complication of radiation therapy for cancers, and may have a devastating effect on the patient’s quality of life (QOL). Advances in histopathology and neuro- radiology have helped shedding light on this problem more comprehensively, but effective therapeutic interventions have been lacking. It was once regarded as a progressive and irreversible disease, however, in the past twenty years, with the application of intensity-modulated radiation therapy (IMRT), both the incidence and severity of CRN has declined. In addition, new treatment modalities such as the use of bevacizumab-a humanized monocloncal antibody against vascular endothelial growth factor (VEGF), monosialotetrahexosylganglioside (GM1), and nerve growth factor (NGF), have been reported to be effective in successfully reversing cerebral radiation necrosis. This review describes up-to-date information regarding the incidence, pathophysiology, management and prognosis of temporal lobe necrosis (TLN) after IMRT for nasopharyngeal carcinoma.